Fiscal Discipline and Exchange Rate Regimes Evidence From the Caribbean - Duttagupta, Rupa (International Monetary Fund, 2006)
This paper assesses the nature of fiscal discipline under alternative exchange rate regimes. First, it shows in a simple theoretical framework that fiscal agencies under a currency union with a fixed exchange rate can have the largest incentive to overspend or ""free-ride"" (compared to those under other exchange rate regimes) owing to their ability to spread the costs of overspending in terms of the inflation tax across both time-given the fixed exchange rate-and space-given the currency union. In contrast, such free-riding behavior does not arise under flexible regimes owing to the immediate inflationary impact of spending. Next, empirically, it shows that fiscal stances in countries with fixed pegs and currency unions regime demonstrate greater free-riding behavior than countries with more flexible regimes in 15 Caribbean countries during 1983-2004